Numerical Simulation of Thermal-Hydrodynamic Behavior within Solar Air Collector (Journal of Engineering, 2018)
Solar collectors, in general, are utilized to convert the solar energy into heat energy, where it is employed to generate electricity. The non-concentrating solar collector with a circular shape was adopted in the present study. Ambient air is heated under a translucent roof where buoyant air is drawn from outside periphery towards the collector center (tower base). The present study is aimed to predict and visualize the thermal-hydrodynamic behavior for airflow under inclined roof of the solar air collector, SAC. Three-dimensional of the SAC model using the re-normalization group, RNG, k−ε turbulence viscus model is simulated. The simulation was carried out by using ANSYS-FLUENT 14.5. The simulation results demonstrated that at same insolation; airflow, ground and air temperatures increase when the collector radius decreases towards the collector center. The ground temperature and air velocity increase, while airflow temperature decreases when the inclination angle increases from 0° to 20° due to changing in airflow movement. More decreasing in airflow temperature has been occurred when the inlet height increases from 0.1m to 0.25m. The simulation results were validated by comparing with the experimental data. In conclusions, the obtained results showed the capability of producing warm airflow to generate electricity in Baghdad city.